Oracle E-business suite development and extensibility handbook - 498000 Passi, Anil; Ajvaz, Vladimir (Emeryville, Calif. : McGraw-Hill/Osborne ; London : McGraw-Hill [distributor])
Includes bibliographical references (p. 3) and index.